PENGENDALIAN SIKLUS ESTRUS DAN PENGATURAN PERKAWINAN PADA TERNAK KAMBING DI DUSUN AIR ALI DAN WARINGIN CUP DESA RUMAH TIGA, KOTA AMBON - Jusak Labetubun; Demianus Ferdinand Souhoka; Juliet Bercomien Papilaya (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2023)
PkM activities aim to apply technology to control the cycle and regulate mating in goats. The goal of this activity is for goat breeders to easily control and marry theis goats. The method is counselling and injection of the litotrof hormone PGF2Alfa intramuscularly, The type of goat used was kacang goat aged 3-4 years as many as 9 heads. The goats were randomly divided into two treatment groups, namely the group that received 0,6 ml PGF2Alfa and the group that received 0.5 ml PGF2Alfa. The injection activity was carried out in two stages. The first stage uses 0.6 ml of PGF2Alfa in all livestock without knowing which phase of the estrous cycle the cattle are used in. The second stage was carried out on the 15th day according to predetermined grouping where the group that received 0.6 ml treatment was 5 individuals and the group that received 0.5 ml was 4 individuals. The results obtained showed that within 3.59 and 42.45 hours, all livestock showed ssign of estrus simultaneously. PkM activities concluded that both controlling the estruos cycle using 0.6 ml of PGF2Alfa and using 0.5 ml of PGF2Alfa simultaneously showed signs of estrous and ready for mating.